Gestión administrativa en la Empresa Produagro S. A. en la ciudad de Babahoyo. - García Bueno, Willians Ismael (2022)
The current case study was carried out in the company Produagro S.A in the city of Babahoyo, a branch of the parent company located in the canton of Ventanas, the subject of study is the administtrative management that froms the essential bases in any organization. The purpose of this study is to analyze the most important aspects of the organizational functioning practices of the aforementioned entity and thus be able to identify weaknesses that need improvement to achieve optimal organizational resuts. The methodological framework includes a descriptive qualitative project using two types of research: documentary and field; the method used is deductive through the interview as a research technique where information is collected from primary sources. The conclusions have shown that the investigations show that there is no efficient administrative management in business Produagro S.A mainly due to the inadequate application of administrative processes, which affects the motivation of colleagues and therefore their professional perfonmance. All these aspects limit the achievement of the company’s objetives.